Gaya Kepemimpinan Kepala Sekolah Untuk Meningkatkan Disiplin Kerja Guru Di SD Negeri 39 Dan 43 Bengkulu Selatan - sutanto, sutanto; Danim, Sudarwan; Putri Kartiwi, Asti (Manajer Pendididikan, 2025)
This study aims to describe the leadership style of school principals to improve teacher discipline, which includes the authoritarian leadership style of school principals, the democratic leadership style of school principals, and the laissez-faire leadership style of school principals to improve teacher discipline. The method used is qualitative descriptive with techniques of interviews, observations, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which consists of data reduction, data presentation, and data verification. The research results are as follows: 1) The authoritarian leadership style of the principals of SD Negeri 39 and 43 in South Bengkulu is not used as the primary pattern but rather as a situational strategy applied when conditions demand firmness, full control, and quick decisions, especially in dealing with repeated disciplinary violations, emergency situations, or conflicts among teachers. 2) Democratic leadership style is applied by the principals at SD Negeri 39 and SDN 43 in South Bengkulu and has proven effective in improving teacher discipline while fostering a collaborative work culture. This leadership style is demonstrated through open communication, active teacher participation in policy formulation, and decision-making based on consensus. 3) The laissez-faire leadership style of the principals at SDN 39 Bengkulu Selatan and SDN 43 Bengkulu Selatan is implemented selectively and adaptively in accordance with the conditions of the teachers and the needs of the school. This leadership style is considered effective when applied to teachers who possess high professionalism, discipline, and independence.